La Isla Archives of a Tragedy - Stelzner, Uli (Germany, 2009)
At the end of the 20th century in Guatemala the army and police killed and abducted hundreds of thousands of people, but the unprecedented genocide in Central America’s modern history went unpunished. However, in July 2005 a huge explosion in the Guatemalan capital led to the discovery of the historic archive of Guatemala’s national police. On the grounds of where a police academy now exists, there was once a secret prison operated by the notorious Policía Nacional squads. It was here that millions of documents appeared. The film traces the story of a tragedy and finds proof of inconceivable atrocities. It is also a movie about a young generation of archive workers willing to free their society from the stranglehold of its own history.